Factors that influence organizational citizenship behavior at Agensi Kaunseling & Pengurusan Kredit / Fatin Syahirah Faizul Maulud - Faizul Maulud, Fatin Syahirah (Faculty of Business and Management, 2018)
Organizational Citizenship Behavior (OCB) is a fundamental element in ensuring organization’s survival and productivity. OCB has exists since decades ago but it is still in the emerging of development. The objective of this study is to determine the factors that give impact to organizational citizenship behavior where the following factors are altruism, conscientiousness, sportsmanship, civic virtue and courtesy. Moreover, the researcher also investigates the significant relationship between all independent variables and dependent variables. For data collection, the researcher distributes questionnaires as primary data to get feedback from the employees at AKPK. Furthermore, 113 respondents from various departments participated in this study. Findings showed that all independent variables have positive relationship with dependent variables. On the other hand, multiple regression test displayed that only altruism, sportsmanship and courtesy are significant in this study whereas other independent variables such as conscientiousness and civic virtue are not. The findings of the study will give tremendous benefits to the Agensi Kaunseling & Pengurusan Kredit (AKPK). The organization can determine the most preferred behaviors by employees and focus on enhancing those behaviors. The employees also will gain knowledge and better understanding about good behaviors that should be implemented at the workplace.